Pharmacological Versus Non-Pharmacological and Ancillary Mechanisms in Eye Drops Used in the Treatment of Glaucoma - Marchesi, Nicoletta; Fahmideh, Foroogh; Barbieri, Annalisa; Racchi, Marco; Pascale, Alessia; Govoni, Stefano (Frontiers in Drug Safety and Regulation, 2022)
Medical Devices Made of Substances (MDMS) are a valuable therapeutic resource available in various pharmaceutical forms. MDMS are marketed to treat different diseases and the advantages and benefits of the use of these products can be claimed, once proven their clinical activity. What are the differences between MP and MDMS? The substantial difference lies in the mechanism of action: MP are based on pharmacological, metabolic, and immunological actions while MDMS are based on mechanical, or chemical/physical action. Sometimes the boundaries are not well defined and there is a need for a reassessment and a consensus on the underlying concepts and definitions, also in the light of the increasing ability to recognize molecular mechanisms underneath the action of several substances not acting through an easy recognizable unique target (as a receptor, for example). In the present paper, we discuss the role of eye drops as an example of MDMS used in glaucoma, a widely diffused eye disease. The choice is due to the fact that products used in this field of application and containing similar substances are marketed either as medicinal products or as medical devices or as food supplements. Accordingly, it is important to underscore in the various cases what is the principal mode of action and the contribution of additional mechanisms as derived, for example, from system pharmacology data. Their analysis may help to exemplify some of the problems around the border between MDMS and MP suggesting the need for new definitions and regulatory decisions.